Our guest: Selva Almada: “My writing is influenced by what I hear, what I see in the street, but also by memories and reading” - United Nations Educational, Scientific; Cultural Organization; Lucía Iglesias Kuntz (The UNESCO Courier, 2025)
In a country where the literary scene is concentrated in the capital, writer Selva Almada claims to belong to the “interior” of Argentina, the province where she grew up. A finalist for the prestigious Booker Prize in 2024, she is one of the most powerful voices in Argentine literature, translated into many languages. She is also one of the region’s most influential feminist intellectuals.